Corporate governance in the Hungarian banking and insurance sector - Ádám Angyal; Júlia Csanda (Journal for East European Management Studies, 2006)
The financial sector has been one of the most profitable sectors of the Hungarian economy for years. The same financial sector which, in the nineties, underwent a painful and very expensive consolidation period. This matter of fact has drawn the researchers' attention to that particular sector. Is this the result, or at least partly, of outstanding corporate governance structures and practices? Making use of the questionnaire developed by the University of Chemnitz, the researchers wanted to get a detailed picture about the Hungarian financial sector's corporate governance structures and its approach of the corporate governance topic. Corporate governance is not the greatest preoccupation of the Hungarian financial institutions, their outstanding financial results are not due to outstanding governance structures, and they broadly have a legal approach of this topic. – – Der Finanzsektor ist seit Jahren einer der profitabelsten Sektoren in der ungarischen Wirtschaft. Der gleiche Finanzsektor, der in den 90er Jahren eine schmerzhafte und sehr aufwändige Konsolidierungsphase hatte. Diese Tatsache hat die Aufmerksamkeit der Forscher auf diesen besonderen Sektor auf sich gezogen. Ist dies das Ergebnis oder zumindest teilweise, von außergewöhnlichen Corporate Governance Strukturen und Praktiken? Ausgehend von einem Fragebogen, der an der TU Chemnitz ausgearbeitet worden ist, wollten die Forscher ein detailliertes Bild über die Corporate Governance Strukturen des ungarischen Finanzsektors erhalten sowie über dessen Herangehensweise and die Corporate Governance Thematik. Corporate Governance hat nicht die höchste Priorität bei den ungarischen Finanzinstitutionen, ihre außergewöhnlichen finanziellen Ergebnisse haben sie nicht aufgrund von außergewöhnlichen Governance Strukturen, und allgemein haben sie eine rechtliche Herangehensweise auf diese Thematik.
Keywords: 650; Financial sector; Corporate Governance; Hungary; banking; insurance